Bank Integration and Business Volatility in the U.S. - Don Morgan; Bertrand Rime; Philip Strahan (Swiss National Bank, Study Center Gerzensee, 2001)
We investigate how bank migration across state lines over the last quarter century has affected the size and covariance of business fluctuations within states. Starting with a two-state version of the unit banking model in Holmstrom and Tirole (1997), we conclude that the theoretical effect of integration on business cycle size is ambiguous, as some shocks are dampened by integration, but others are amplified. Empirically, we find that integration diminishes employment growth fluctuations within states, and decreases the deviations in employment growth across states. Business cycles within states become smaller with integration, in other words, but more alike. Our results for the United States bear on the financial convergence underway in Europe, where banks remain highly fragmented across nations.
Keywords: G21; E44; G28; 330; Interstate banking; Business cycle; Financial integration; Finanzsystem; Strukturwandel; Marktintegration; Fusion; Regionale Konjunktur; Theorie; USA